Method for registration of vaccines for covid 19, through nfc technology - Auccahuasi, Wilver (2022)
“ In these times of pandemic caused by Covid-19, new ways of dealing with the effects of the virus emerge, for this reason multiple measures are being carried out with the intention of mitigating its effects in the event of a possible contagion, which is why vaccinations are being carried out massive in order to be able to defend oneself against potential contagions, in this work an application made using the NFC communication protocol that mobile devices have is shown, as a result the demonstration of the use of the application is presented, where it reflects the data to be entered and can be viewed from any device“